Pendidikan Islam Dalam Diaspora Iblis Pasca Terusir Dari Surga - Robingun Suyud El Syam; Hendri Purbo Waseso (Pusat Riset dan Inovasi Nasional, 2023)
Devils originally had a high position, including the leaders of the Angels, but why did they become the lowest creatures in the end. Through the thematic interpretation approach, facts are found, the pride of the Devil makes him go against God's commandments, results in being expelled from heaven, bearing the cursed status. So, he and his descendants are determined throughout their lives to mislead humans to become friends later in hell. So whoever is firm in God's way will be noble like an angel, on the other hand whoever follows the path of Satan will fall into the abyss of humiliation.